Genome-wide identification and expression analysis disclose the pivotal PHOSPHATIDYLETHANOLAMINE BINDING PROTEIN members that may be utilized for yield improvement of Chenopodium quinoa - Wu, Qi; Bai, Xue; Nie, Mengping; Li, Li; Luo, Yiming; Fan, Yu; Liu, Changying; Ye, Xueling; Zou, Liang (Frontiers in Plant Science, 2023)
Quinoa (Chenopodium quinoa) is a prospective orphan crop that needs yield improvement. Previous studies indicate PHOSPHATIDYLETHANOLAMINE BINDING PROTEIN (PEBP) family genes are highly associated with the key agronomic traits of crops. Characterizing the pivotal PEBP genes will speed up the domestication and yield improvement of quinoa. Previous investigations on PEBP genes of Chenopodium species indicated that, the PEBP genes, despite in the same subclade, may have experienced functional diversification. Especially, the allotetraploidy (AABB) and numerous segmental duplications and chromosomal rearrangements in quinoa make it more difficult to understand the functions of PEBP genes. More recently, 6 quinoa FT subfamily genes were predicted to be related to flowering of quinoa. However, investigation on the whole PEBP family members is still lacking. In this study, we obtained 23 PEBP genes, including 5 MFT, 11 FTL and 7 TFL genes. We found 7 orthologous gene pairs, from sub-genome A and sub-genome B, respectively, showing collinearities with sugar beet. Evolution analysis on PEBP genes of two quinoa sub-genomes, sugar beet and relatives of diploid ancestors indicated that, the reasons for gene duplication events varied and 4 tandem duplications are the major reason for PEBP family expansion. Tissue-specific expression analysis suggested that expression patterns are mostly differing between orthologous gene pairs. Analysis on gene expressions at 6 stages suggested the possible positive roles of CqFTL1/CqFTL2, CqFTL5, CqFTL8, CqFTL6/CqFTL9 and CqTFL6/CqTFL7, and negative roles of CqTFL1/CqTFL2/CqTFL3, CqTFL4/CqTFL5 in inflorescence branching. Expression analysis in ABA-treated seed, in combination with the cis-acting element distribution analysis, indicated that CqMFT2, CqMFT3 and CqMFT4 may regulate seed germination via ABA signaling. Observations on responses to night break and photoperiod changes highlighted the roles of CqFTL5 and CqFTL8 under SD, and CqFTL6 under LD for quinoa flowering. Further, co-expression network analysis indicated that 64 transcription factors may act upstream of CqFTL5 and CqFTL8 to regulate flowering. Together, this study will help us identify the pivotal PEBP genes that may be utilized for quinoa breeding in future.